Insights into the triplet photochemistry of atmospheric aerosol and subfractions isolated with different polarity. (1st December 2022) - Li, Jinwen; Chen, Qingcai; Guan, Dongjie
Abstract: Atmospheric aerosols contain organic compounds that can form triplet organics ( 3 C*) excited by sunlight, which plays a significant role in the aging process of aerosols. The formation characteristics of 3 C* of aerosol components with different polarities were investigated, including highly polar water-soluble matter (HP-WSM), humic-like substances (HULIS), and methanol-soluble matter (MSM). Carbon analysis, probe method and electron paramagnetic resonance were used to investigate the photochemical properties of ambient samples. The coupling effect of generation of 3 C* and reactive oxygen species (ROS) between different aerosol components was also examined. The results showed that the 3 C* generation characteristics are strongly dependent on the polarity of these components. HULIS has the strongest generation ability of 3 C*, and the MSM contributes the most to the total generation of 3 C*. It was found that the high-energy triplet states ( E T ≥ 250 kJ mol −1 ) of HULIS and HP-WSM components account for up to 80% of the water soluble components. These 3 C* have an important contribution to the photochemically generation of ROS, and the generated ROS of different components are also different, which is determined by the chromophore composition of complex organic compounds. A tyrosine-like chromophore is the main substance leading to the formation of water-soluble 3 C*, while the highly oxidized HULIS chromophore plays a leading role in the water-insoluble component. This study also found that there is a coupling effect between HP-WSM and HULIS on 3 C* and ROS generation. The generation rate of 3 C* increases by about 40% after mixing, but the generation of 1 O2 is severely reduced. In general, this study provided deep insights into the generation characteristics and aging impact of the triplet state on atmospheric aerosols. Graphical abstract: Image 1 Highlights: 3 C* generation is dependent on the polarity of aerosol components. Aerosol HULIS has the strongest generation ability of 3 C*. The 3 C* generated by HULIS are mainly high energy ( E T ≥ 250 kJ mol −1 ). Aerosol 3 C* had an important contribution to the ROS generation. There is a coupling effect between HP-WSM and HULIS on 3 C* generation.